Flipped-SAC dan Jurnal Belajar untuk Meningkatkan Hasil Belajar dan Partisipasi Siswa dalam Pembelajaran Biologi Sel - Witheastutie, Andri (Universitas Muria Kudus, 2022)
In this classroom action research intends to improve student participation and learning outcomes in MIPA 3 class, which was previously the most passive and had the lowest learning outcomes. The research employs the flipped classroom learning methodology, wherein the learning media is bundled in the SAC (Smart Apps Creator) program and managed via a learning journal. Two rounds of classroom action research were conducted. The participation rate was high, but it did not reach 100 percent, and the learning diary was unsatisfactory throughout the first cycle. Furthermore, in the second cycle, several enhancements were made. The average value of learning outcomes increased significantly, from 62.17 before the intervention to 81.33 in cycle 1 and 85.15 in cycle 2. At the beginning of the study, the student's response to this learning paradigm was less favourable, around 33% of students believed the model flipped. This is too difficult to follow, becomes a burden, and exacerbates an already difficult duty. some kids can't open SAC media since the cellphone does not support it. But by some direction and agreement in the end all can go smoothly. As a consequence of the comprehensive daily assessment, the action class received the highest average score compared to its 10 parallel classes. Flipped classroom is proved to establish a habit of liking to learn, even though it was initially rejected.